X-Similarity Comparison by using Wordnet - Shahreen Kasim; Nurul Aswa Omar; Nurul Suhaida Mohammad Akbar; Rohayanti Hassan; Masrah Azrifah Azmi Murad (Society of Visual Informatics, 2017)
Semantic web is an addition of the previous one that represents information more significantly for humans and computers. It enables the description of contents and services in machine readable form. It also enables annotating, discovering, publishing, advertising and composing services to be programmed. Semantic web was developed based on Ontology which is measured as the backbone of the semantic web. Machine-readable is transformed to machine-understandable in the current web. Moreover, Ontology provides a common vocabulary, a grammar for publishing data and can provide a semantic description of data which can be used to conserve the Ontology and keep them ready for implication. There are many that used in feature based in semantic similarity. This research presents a single ontology of X-Similarity feature based method.